Effect of high hydrostatic pressure on activity, thermal stability and structure of horseradish peroxidase. (15th June 2022) - Zhang, Sinan; Zheng, Zhenhong; Zheng, Chuyao; Zhao, Yadong; Jiang, Zhuo
Highlights: Horseradish peroxidase activity decreases after high hydrostatic pressure treatment. HHP processing decreases the thermal stability of HRP. The molecular structure of HRP was changed after HHP treatment. HHP treatment can cause HRP molecule agglomeration. Abstract: The mechanism of the high hydrostatic pressure (HHP) effect on horseradish peroxidase (HRP) is still unclear. The activity, thermal stability and structural changes of HRP after HHP treatments were studied in this work. Compared with the untreated sample, the enzyme activity reduces by 36% after 800 MPa processing. The results indicated that the conformation of the enzyme active center changes under pressure. Furthermore, HHP also changes the conformation of disulfide bonds and some secondary structures in HRP. These structural and conformational changes induce decreased activity. In addition, differential thermal scanning (DSC) results showed that the thermal denaturation temperature decreased from 103.74 °C to 85.78 °C after pressure treatment, suggesting HRP molecules formed large aggregates after pressure treatment. In this study, the interaction mechanism between pressure and enzyme was studied as well, and the results can provide some guidance for the application of HHP technology in fruit and vegetable products processing.